Structural, optical and electronic properties of Fe doped ZnO thin films. (September 2015) - Singh, Karmvir; Devi, Vanita; Dhar, Rakesh; Mohan, Devendra
Highlights: FE doping decrease grain size due to accumulation of defects. Surfaces of undoped and doped thin films are smooth and crack free. Band gap reduced with Fe doping due to decrease in transition tail width. Modification in electronic structure is observed with Al doping. Abstract: Fe doped ZnO thin films have been deposited by pulsed laser deposition technique on quartz substrate to study structural, optical and electronic structure using XRD, AFM, UV–visible and X-ray absorption spectroscopy. XRD study reveals that Fe doping has considerable effect on stress, strain, grain size and crystallinity of thin films. UV–visible study determines that band gap of pristine ZnO decreases with Fe doping, which can be directly correlated to transition tail width and grain size. Change in electronic structure with Fe doping has been examined by XAS study.